2020
DOI: 10.1038/s42003-020-0755-1
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-mediated gene correction links the ATP7A M1311V mutations with amyotrophic lateral sclerosis pathogenesis in one individual

Abstract: Amyotrophic lateral sclerosis (ALS) is a severe disease causing motor neuron death, but a complete cure has not been developed and related genes have not been defined in more than 80% of cases. Here we compared whole genome sequencing results from a male ALS patient and his healthy parents to identify relevant variants, and chose one variant in the X-linked ATP7A gene, M1311V, as a strong disease-linked candidate after profound examination. Although this variant is not rare in the Ashkenazi Jewish population a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…1B , C and S1A ). Consistent with increased reactive oxygen species previously described in neural progenitor cells ( Yun et al, 2020 ), we observed a significantly decreased ratio of reduced to oxidized glutathione (GSH/GSSG) in fibroblasts carrying the M1311V mutation compared to two control lines, reflecting an inherent increased state of intracellular oxidative stress ( Fig. S1B ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…1B , C and S1A ). Consistent with increased reactive oxygen species previously described in neural progenitor cells ( Yun et al, 2020 ), we observed a significantly decreased ratio of reduced to oxidized glutathione (GSH/GSSG) in fibroblasts carrying the M1311V mutation compared to two control lines, reflecting an inherent increased state of intracellular oxidative stress ( Fig. S1B ).…”
Section: Resultssupporting
confidence: 88%
“…A variant of ATP7A, ATP7A M1311V has recently been identified in a patient with brachial amyotrophic diplegia/flail arm syndrome (also called man-in-barrel syndrome) with slow-progressing ALS ( Yun et al, 2020 ). ALS is a neurodegenerative disease characterized by loss of motor neurons in the brain, brainstem and spinal cord, along with muscle atrophy ( Al-Chalabi et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of whole-genome sequencing-based gene variant discovery and CRISPR-iPSC-based disease modelling techniques has accelerated the discovery of rare yet highly penetrant ALS-causing novel gene variants which only certain ethnic groups are predisposed to (Yun et al 2020 ). A sizeable fraction of the published studies have reported the utilization of CRISPR/Cas9-corrected patient-derived iPSC lines to generate isogenic disease models.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…A recent study based on whole-genome sequencing identified one demographic variant in the X-linked ATP7A gene, M1311V as a strong candidate in pathogenesis. They corrected this mutation using CRISPR-Cas9 in iPSCs-derived from the patient's fibroblasts and demonstrated significant restoration of the neuronal defects in these corrected iPSC-derived motor neurons [85]. It has been reported recently that, human motor neurons with CRISPR-Cas9 generated SOD1-G93A mutation showed disease-relevant phenotypes including SOD1 aggregation, axonal degeneration, and aberrant synaptic functions [86].…”
Section: The Use Of Gene Editing For Alsmentioning
confidence: 99%